Cryopreservation of the Australian species Macropidia fuliginosa (Haemodoraceae) by vitrification - Turner, Shane; Tan, B.; Senaratna, T.; Bunn, E.; Dixon, Kingsley; Touchell, D.H. (CRYO LETTERS, 2000)
Somatic embryos were used to develop a cryopreservation protocol for Macropidia fuliginosa, a commercially-important species endemic to the south-west of Western Australia. Somatic embryos were allowed to develop from embryogenic callus for three weeks on an kinetin medium prior to processing. These were transferred and cultured on a agar solidified basal medium supplemented with 0 to 0.6 M sorbitol for 2 d prior to incubation in Plant Vitrification Solution Two (PVS2). Following this, embryos were then washed in 1 M sucrose solution (treated controls) or cooled in liquid nitrogen (LN). Cooled embryos were then warmed and washed in sucrose solution. Highest survival for cooled treatments (67.3%) was achieved by preculture with 0.4 M sorbitol, then incubation in PVS2. Further experimentation varying pre-culture duration (2 or 3 d) and incubation on either glycerol (0.8 M) or sorbitol (0.4 M) indicated that very high survival (90.6%) of embryos was achievable by adopting a 2 d preculture period on 0.8 M glycerol. The phenotype and growth rates of plants obtained using this protocol were similar to those of parent plants. This optimised procedure was then applied to tissue culture-derived shoot apices of the same clone also resulting in a high survival rate (84.4%).